Extraction and characterization of cellulose nanocrystals from tea leaf waste fibers as a filler in poly(lactic acid) bio-nanocomposites - Abdul Rahman, Nur Hayati (2018)
Poly(lactic acid) (PLA) is known to be a very useful material in replacing the petrochemical-based polymer in the packaging sector due to its biodegradability and good mechanical characteristics. Despite the impressive behaviors of PLA, the low brittleness of itself has limited the usage of this material. Thus, cellulose nanocrystals (CNCs) was extracted from tea leaf wastes fibers (TLWF) to incorporate into PLA, enhancing the performance of polymer nanocomposites while keeping the environment safe. This research was conducted to explore the utilization of TLWF as a source for the production of CNCs and its uses as a filler on PLA. TLWF was first treated with alkaline, followed by bleaching before being hydrolyzed with concentrated sulfuric acid. The materials attained after each step of treatments were characterized. From Fourier transform infrared spectroscopy (FTIR), the peak at 1716 represents C=O stretching disappeared in the spectra after the alkaline and bleaching treatments indicated that hemicellulose and lignin were almost discarded from the fiber. The reduction intensity of the absorption band at 1236 cm−1which accredited to the C–O stretching vibration of the lignin and xylan occurred due to the decreasing of lignin and a small hemicellulose contents from TLWF. Meanwhile, the thermal stability of CNCs was decreased due to the replacement of hydroxyl groups by sulfate groups during hydrolysis. The scanning electron microscopy (SEM) showed the defibrillation of fibers occurred after the treatments, increasing the susceptibility of fiber for acid hydrolysis. The crystallinity index of fiber also increased from 41.5% to 83.1% and from transmission electron microscopy (TEM), the rod-like shaped CNCs with an average diameter of 7.97 ± 1.09 nm was revealed. Then, the resultant CNCs were used as filler in PLA bio-nanocomposites via solvent casting method. The different contents of CNCs between 0.5 to 5 wt % were filled. The mechanical properties of films were analyzed through the tensile properties. The optimum value of tensile strength and modulus was achieved when 2.0 wt % of CNCs content was incorporated into the matrix. As a conclusion, CNCs can be produced from TLWF and can be used as a filler for PLA at the 2.0 wt % of CNCs loading.